2019
DOI: 10.3390/jcm8071001
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Sestrins in Neurodegenerative Diseases: Counteracting Oxidative Stress and Beyond

Abstract: Low levels of reactive oxygen species (ROS) are critical for the operation of regular neuronal function. However, heightened oxidative stress with increased contents of oxidation markers in DNA, lipids, and proteins with compromised antioxidant capacity may play a harmful role in the brain and may be implicated in the pathophysiology of neurodegenerative diseases. Sestrins, a family of evolutionarily-conserved stress-inducible proteins, are actively regulated by assorted stresses, such as DNA damage, hypoxia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 106 publications
1
31
2
Order By: Relevance
“…Ubiquitin-binding protein p62 enhances Keap-1-Nrf2 dissociation and facilitates degradation of Keap1 by p62-dependent autophagy, further stimulating the antioxidant response [ 88 , 89 ]. In addition, sestrins (SESNs), proteins involved in protecting cells from oxidative stress also promote p62-dependent autophagic degradation of Keap-1 [ 90 ]. Therefore, there is a close relationship between oxidative stress and autophagy where oxidative stress can induce autophagy through various mechanisms and vice-versa [ 36 , 91 ].…”
Section: The Relationship Between Reactive Oxygen Species and Autophamentioning
confidence: 99%
“…Ubiquitin-binding protein p62 enhances Keap-1-Nrf2 dissociation and facilitates degradation of Keap1 by p62-dependent autophagy, further stimulating the antioxidant response [ 88 , 89 ]. In addition, sestrins (SESNs), proteins involved in protecting cells from oxidative stress also promote p62-dependent autophagic degradation of Keap-1 [ 90 ]. Therefore, there is a close relationship between oxidative stress and autophagy where oxidative stress can induce autophagy through various mechanisms and vice-versa [ 36 , 91 ].…”
Section: The Relationship Between Reactive Oxygen Species and Autophamentioning
confidence: 99%
“…Recent studies suggest that Sestrins improve longevity and elderly health by suppressing ROS, regulating autophagy activity and protecting metabolic dysfunction in muscle, heart and brain (Rai et al, 2018;Chen et al, 2019;Cordani et al, 2019;Fan et al, 2020;Liu et al, 2020;Segales et al, 2020;Sun et al, 2020). The level of Sestrins expression is downregulated in aged men although it has no clear correlation with autophagy activity, mTORC1 activity and antioxidant regulation (Zeng et al, 2018a).…”
Section: Sestrins In Environmental Stress and Agingmentioning
confidence: 99%
“…These studies indicate that maintaining the homeostatic level of Sesn2 is protective against cardiovascular aging (Liu et al, 2020;Sun et al, 2020). Sesn2 promoted autophagy in the brain and prevented neurodegenerative diseases by alleviating oxidative stress (Chen et al, 2019;Luo et al, 2020). Sesn2 protects neuronal cells from cerebral ischemia-reperfusion injury by increasing Nrf2, Srx1, and thioredoxin (Trx) 1 (Zhang and Zhang, 2018).…”
Section: Sestrins In Environmental Stress and Agingmentioning
confidence: 99%
“…Sestrin (Sesn) family members, including Sesn1, Sesn2, and Sesn3 in mammals, are proteins that regulate oxidative stress both in vivo and in vitro [6,7]. Sesn is widely present in a variety of tissues and organs, and its expression is majorly regulated by oxidative stress levels and, to a lesser extent, by inflammatory responses, aging, and other pathophysiological effects [8][9][10]. A number of studies have confirmed that Sesns are involved in the development and progression of various diseases, by regulating oxidative stress.…”
Section: Introductionmentioning
confidence: 99%